Application and Research of Health Monitoring System of Xiangshan Port Bridge. Issue 3 (April 2021) - Gao, Jian; Li, Dongming; Feng, Yafei; Wan, Lijun; Wu, Guojun
Abstract: The core of bridge development in China is from construction to maintenance. Therefore, the structural health monitoring system (SHMS) which can monitor and evaluate the bridge structure condition in real time has attracted wide attention. In this paper, according to the management and maintenance requirements of Xiangshan Port Bridge, the health monitoring system is designed, including sensor subsystem, data acquisition and transmission subsystem, integrated monitoring and evaluation subsystem. Afterwards, the SHMS set up, including the installation of sensors, debugging of system, development of Web User Interface and other work. After trial operation, the results show that the SHM of Xiangshan Port Bridge runs smoothly and can monitor changes and trends of state parameters of bridge structure in real time and dynamically, which provides a scientific basis for the evaluation of bridge structure state and facilitates overall lifetime management of the bridge.